Blind Spots in Public Ethics and Integrity Research: What Public Administration Scholars Can Learn from Aristotle. (3rd May 2020) - van Steden, Ronald
Abstract : The discourse on 'good governance' is of growing importance in the public integrity and public values literature. However, it is not so simple to discern what 'good governance' actually means. This paper delves into the work of the ancient philosopher Aristotle who has influenced a stream of practice theories underlining the significance of virtues (instead of values) and of 'doing things well'. It specifically explores the relevance of Aristotelian philosophy for public professionals by emphasising the central virtue of practical wisdom (phrónêsis or prudence) that sustains craftsmanship as an action-oriented means to achieving viable results. Public integrity, defined as an overarching virtue of a practical sort, contains strong parallels with this Aristotelian phrónêsis which aims to achieve excellence in professional practices – even to the point of being modest if necessary – and assures continuous reflection on public professionals' quality of work. In other words: public professionals must be persons of integrity – of moral wholeness and soundness – who are virtious in aligning their judgements with a vision of the good life from which society and citizens can flourish.